Emotionally Focused Therapy in the Context of Addictions: A Case Study. (July 2018) - Fletcher, Kara; MacIntosh, Heather
Substance addictions represent a serious social problem in North America, negatively impacting family relationships and couple functioning. Research is increasingly considering the potential for couple therapy as a model within this context. Issues presented by an addiction can be exacerbated by other issues present in a couple relationship. Using a case study design, this research study explored a proposed theoretical extension of emotionally focused couple therapy (EFT) in the context of substance addictions. Four couples were recruited, and an analysis of the therapeutic process and their experiences is presented. Comparisons between the normative EFT treatment model and the theoretical extension are made and recommendations are provided for further adaptations to the model. Results from this study indicate the important place of couple therapy in addiction treatment.